Bilingualism in a Case of the Non-fluent/agrammatic Variant of Primary Progressive Aphasia - Karpathiou, Nomiki; Papatriantafyllou, John; Kambanaros, Maria (Frontiers in Communication, 2018)
There is a growing body of research on language impairment in bilingual speakers with neurodegenerative diseases. Evidence as to which language is better preserved is rather inconclusive. Various factors seem to influence language performance, most notably age of acquisition, level of proficiency, immersion and degree of exposure to each language. The present study examined fluency, lexical, discourse and grammatical abilities of a Greek-French late bilingual man with the non-fluent/agrammatic variant of primary progressive aphasia (nfvPPA). Speech samples derived from three different narrative tasks in both languages were analyzed using quantitative production analysis (QPA) and fluency measures. The first aim of the study was to compare the participant’s connected speech production to that of Greek-speaking normal controls. The second aim was to determine whether Greek (L1) and French (L2) were differentially impaired. To our knowledge, this is the first report of connected speech deficits in a Greek-speaking patient with PPA and the first study which uses QPA to compare L1 and L2 narratives in a bilingual speaker with PPA. Compared to neurologically healthy controls, our participant was impaired in lexical, discourse and grammatical productivity measures, but did not differ in measures of grammatical accuracy. The presence of dysfluencies, reduced speech rate and simplified syntax is consistent with the pattern of impairment reported for the nfvPPA. Results showed that narrative production measures did not differ significantly between languages. However, they suggest a slightly worse performance in his second, non-dominant, language despite a similar pattern of impairment in both languages. Lengthy exposure to L2 and regular activation of L2 through daily use may explain the preservation of discourse abilities in his non-dominant language. This study calls attention to factors such as language dominance, proﬁciency, patterns of use and exposure to a language. These factors play a key role in assessing bilingual individuals with PPA and making clinical decisions.